HERITAGE AWARENESS STRATEGY ON THE UNESCO-LISTED KEDAH HERITAGE ASSETS AMONG SCHOOL STUDENTS IN KEDAH, MALAYSIA - Wan Shamsuddin, Wan Iskandar Zulkarnain; Said, Shahrul Yani; Harun, Siti Norlizaiha (PLANNING MALAYSIA, 2024)
As Malaysia’s oldest state, Kedah has a long and illustrious history. Its innumerable heritage assets deserve to be protected as part of a conservation effort for the sake of the country’s history and future generations. Lack of heritage-awareness among the community may result in the utter loss of heritage evidence, impeding the identity and pride in local communities as well as economic opportunity in the tourism industry. The aim of this paper is to develop a holistic ‘awareness strategy framework’ on UNESCO-listed Kedah heritage assets (KHAs) among school students in Kedah. Two (2) objectives have been established, namely: 1) to discover the principles of the provision of heritage-awareness strategy for heritage assets with global status, and 2) to ascertain the state of heritage-awareness level among school students on KHAs. A mixed-method analysis was employed involving a literature review and a state-wide survey with 676 school students to assess their awareness on KHAs and related matters. The data revealed alarming results, denoting low awareness on KHAs among the respondents. The findings further offer several recommendations on the appropriate strategy and action plans to enhance heritage-awareness. It is deemed that the implementation must begin with the establishment of a dedicated management body empowered under the state’s statutory act, which will be responsible for heritage-awareness creation via its public education system.